2016
DOI: 10.1002/cjce.22614
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and phase behaviour of Moringa oleifera seed oil using compressed propane

Abstract: This study reports the oil extraction efficiency using Moringa oleifera seed and pressurized propane, new experimental data for phase transition of the binary system {n-propane þ Moringa oleifera oil}, and the profile of fatty acid compositions of the extracted Moringa oil. During the present study, the knowledge of the phase behaviour proved to be of great importance to optimize supercritical extraction using pressurized fluid. This project also compares the classical Soxhlet method including mathematical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“… 0.25 mm of cyano-propyl separates fatty acids in Moringa oleifera seeds, which are rich in oleic acid. [98] The contents of soybean oil are also amenable to this method. A Shimadzu Rtx-Wax capillary column (30 m  0.32 mm i. d.  0.25 mm), separates linoleic and oleic acid, as well as linolenic, stearic, and palmitic acids.…”
Section: Methods Relating the Effective Carbon Number To The Detector...mentioning
confidence: 99%
See 1 more Smart Citation
“… 0.25 mm of cyano-propyl separates fatty acids in Moringa oleifera seeds, which are rich in oleic acid. [98] The contents of soybean oil are also amenable to this method. A Shimadzu Rtx-Wax capillary column (30 m  0.32 mm i. d.  0.25 mm), separates linoleic and oleic acid, as well as linolenic, stearic, and palmitic acids.…”
Section: Methods Relating the Effective Carbon Number To The Detector...mentioning
confidence: 99%
“…× 0.25 mm of cyano‐propyl separates fatty acids in Moringa oleifera seeds, which are rich in oleic acid. [ 98 ] The contents of soybean oil are also amenable to this method. A Shimadzu Rtx‐Wax capillary column (30 m × 0.32 mm i.d.…”
Section: Applicationsmentioning
confidence: 99%
“…The use of carbon dioxide (CO 2 ) eliminates the need for extensive heating while extracting thermolabile chemicals. Numerous studies have reported the extraction of oils and their active components using high-pressure gases (CO 2 and propane) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-known fact that Moringa plants (leaves and fruits) were grown as for skin sanitation, an energy source and also to relieve tension [ 8 , 9 ]. Innumerable reports have discovered that MOL has numerous significant merits, such as antioxidant, antimicrobial, anticancer, anti-inflammatory, antiulcer, antihypertensive, anti-urolithic, anti-asthmatic, antidiabetic, analgesic, anti-aging, diuretic, cardiovascular, hepatoprotective, hypoglycemic and immunomodulatory characteristics [ 10 , 11 , 12 , 13 ]. The hypotensive, antibacterial and anticancer efficacies of the MOL leaves and fruits are due to the presence of sundry distinctive chemical compounds (benzyl glucosinolate, niazimicin, benzyl iso-thiocyanate complexes and pterygospermin) in their structure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all extraction mechanisms experience several restrictions in terms of using a large amount of harmful organic solvents, sample production proceedings and cost [ 13 ]. To get better results, LIBS has emerged as an efficient approach for the identification and quantification of elemental compositions from different medicinal plant extractions.…”
Section: Introductionmentioning
confidence: 99%